Determining optimum flake density for feedlot heifers - M.L. May; M.J. Quinn; Brandon E. Depenbusch; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2008)
Escalating costs of natural gas and electrical utilities have greatly increased the cost of flaking grain for feedlots. Energy demand for flaking is inversely related to bulk density of flaked grain; the lighter, more highly processed flakes typically require longer steaming times and greater roll pressures, which ultimately decreases mill. Corn is most commonly flaked to a density of about 28 lb/bushel, and published research results indicate that levels less than 28 lb/bushel afford no further advantage with respect to animal performance. Little information is available concerning the relative feed value of grains flaked to heavier bulk densities. Flaking grains to heavier bulk densities could make it possible to increase mill throughput and reduce energy costs associated with flaking. In this study, our objective was to evaluate milling efficiency and cattle performance when grains were flaked to densities of 28, 32, and 36 lb/bushel.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Heifers; Flaking grains